Latex vascular injection as method for enhanced neurosurgical training and skills - Pérez-Cruz, Julio C.; Macías-Duvignau, Mario A.; Reyes-Soto, Gervith; Gasca-González, Oscar O.; Baldoncini, Matias; Miranda-Solís, Franklin; Delgado-Reyes, Luis; Ovalles, Carlos; Catillo-Rangel, Carlos; Goncharov, Evgeniy; Nurmukhametov, Renat; Lawton, Michael T.; et al. (Frontiers in Surgery, 2024)
Background Tridimensional medical knowledge of human anatomy is a key step in the undergraduate and postgraduate medical education, especially in surgical fields. Training simulation before real surgical procedures is necessary to develop clinical competences and to minimize surgical complications. Methods Latex injection of vascular system in brain and in head-neck segment is made after washing out of the vascular system and fixation of the specimen before and after latex injection. Results Using this latex injection technique, the vascular system of 90% of brains and 80% of head-neck segments are well-perfused. Latex-injected vessels maintain real appearance compared to silicone, and more flexible vessels compared to resins. Besides, latex makes possible a better perfusion of small vessels. Conclusions Latex vascular injection technique of the brain and head-neck segment is a simulation model for neurosurgical training based on real experiencing to improve surgical skills and surgical results.